(Cleaved) CK18 serum and tissue expression levels differentiate acute HCV reinfection from acute rejection in liver allografts. (12th May 2014) - Reis, Henning; Wohlschläger, Jeremias; Hagemann, Sascha; Wenzel, Patricia; Bechmann, Lars P.; Suttorp, Anna‐Carinna; Schlattjan, Martin J.; Herzer, Kerstin; Canbay, Ali; Baba, Hideo A.
Abstract Background & Aims Orthotopic liver transplantation (OLT) is the sole therapeutic option to cure end‐stage liver diseases including HCV‐related cirrhosis. Timely and precise differentiation of relevant acute HCV reinfection from acute rejection after OLT is vital for appropriate therapy. Aim of this study was to evaluate the usefulness of (non‐) invasive apoptosis (M30) and necrosis (M65) determination in the differential diagnosis of acute (and chronic) HCV reinfection vs. acute rejection in liver allografts. Methods Serum samples and liver biopsy tissues were available from 76 patients including a control group (19× NAFL, 19× NASH, 16× acute rejection, 11× acute and 11× chronic HCV reinfection) and were analysed using M30‐ and M65 ELISAs (M30S, M65S) and M30‐immunohistochemistry (M30H). Clinical and serological data were collected. Results M30S, M65S and M30H were highly correlated with diagnostic groups in the total cohort (all P < 0.0001). M30S, M65S and M30H were independently able to differentiate acute HCV reinfection from acute rejection (P = 0.048, P = 0.001, P = 0.010) with moderate to excellent diagnostic accuracy (sensitivity, specificity, cut‐off‐value in M30S: 70%, 75%, 1025 U/L; M65S: 100%, 92%, 1308 U/L; M30H: 73%, 88%, 0.3%). Conclusions M30‐, M65‐ELISAs and M30‐immunohistochemistry are potential useful tools in differentiating acute HCV reinfection from acute rejection facilitating both speed and accuracy of the diagnostic process for the clinician and hepatopathologist. In this context, M65S provided superior diagnostic characteristics compared to M30‐based methods. However, being the first analysis of (cleaved) CK18 serum and tissue expression levels in this context, the results need to be verified in further studies.